Health status biomarkers and hemato-biochemical indices in Nile tilápia - Lorena Bavia; Ana Paula da Silva; Milena Carvalho Carneiro; Melyssa Kmecick; Roberta Pozzan; Juan Esquivel-Muelbert; Lourdes Isaac; Maritana Mela Prodocimo (Comparative Immunology Reports)
Considering the aquatic environment, fish are notorious bioaccumulators of persistent pollutants, and that Oreochromis niloticus (Nile tilapia) is a species of great economic interest and an excellent model for ecotoxicological experimental studies. Because of this, establishing baseline reference parameters for this healthy animal is extremely valuable for comparison. Thus, our aim is to establish reference values for Nile tilapia for comparative purposes for: (i) functional activation of the alternative pathway of the complement system (ACH50), (ii) some serum biochemical parameters of liver, kidney and muscle tissue integrity, and (iii) hematological profile of Nile tilapia under controlled conditions. Juvenile specimens of O. niloticus were obtained from the fish farming and acclimatized for 15 days. Blood samples were collected without and with anticoagulants (heparin and EDTA) and submitted to hematological assays for leukogram and erythrogram evaluation. Serum was used for the alternative complement and biochemical assays. A mean of 137.6 U/mL was found for ACH50, 52.3 U/mL for alanine aminotransferase, 81.7 U/mL for aspartate aminotransferase, 30.3 U/mL for alkaline phosphatase, 4.3 g/dL for albumin, 8.4 mg/dL for urea, 1.9 mg/dL for uric acid, 3654 U/L for total creatine kinase, 1329.9 U/L for creatine kinase MB fraction, 260.2 U/L for lactic dehydrogenase, 227.2 mg/dL for glucose, 5.6 g/dL for total protein, 252.7 mg/dL for triglycerides, 169.5 md/dL for cholesterol, 19.1 mg/dL for high-density lipoprotein, and 12.5 mg/dL for low-density lipoprotein. For all hematological parameters we found a difference between the lack and presence of the anticoagulants, being the lack and heparin the conditions that presented more stability of the cell numbers along the time. Thus, in this study we establish baseline health parameters for Nile tilapia and it will be applied as an essential and comparative tool for monitoring fish health and physiological fitness at various experimental levels, such as bioassays and environmental biomonitoring.